Assessing carbon stocks and accumulation potential of mature forests and larger trees in U.S. federal lands - Birdsey, Richard A.; DellaSala, Dominick A.; Walker, Wayne S.; Gorelik, Seth R.; Rose, Garett; Ramírez, Carolyn E. (Frontiers in Forests and Global Change, 2023)
Mature and old-growth forests (collectively “mature”) and larger trees are important carbon sinks that are declining worldwide. Information on the carbon value of larger trees and mature forests in the USA has policy relevance for complying with Presidential Executive Order 14072 directing federal agencies to define and conduct an inventory of them for conservation purposes. Specific metrics related to maturity can help land managers define and maintain present and future carbon stocks at the tree and forest stand level, while making an important contribution to the nation’s goal of net-zero greenhouse gas emissions by 2050. We present here a systematic method to define and assess the status of mature forests and larger trees on federal lands in the USA that if protected from logging would maintain substantial carbon stocks and growth potential, along with myriad climate and ecological co-benefits. We based the onset of forest maturity on the age at which a forest stand achieves peak net primary productivity. We based our definition of larger trees on the median tree diameter associated with the tree age that defines the beginning of stand maturity to provide a practical way for managers to identify larger trees that could be protected in different forest ecosystems. In assessing these maturity metrics, we found that the unprotected carbon stock in larger trees in mature stands ranged from 36 to 68% of the total carbon in all trees in a representative selection of 11 National Forests. The unprotected annual carbon increment in live above ground biomass of larger trees in mature stands ranged from 12 to 60% of the total increment in all trees. The potential impact of avoiding emissions from logging mature forests is thus significant and would require a policy shift to include protection of carbon stocks and future carbon sequestration as an additional land management objective on federal forest lands.